Assistance in Fattening Goat Farming Business: Diversification Strategy and Productivity Improvement "Gus Shor Farm" Kanugrahan Maduran Lamongan Village - Hamid, Ahmad Munir (Sahwahita: Community Engagement Journal, 2024)
The development of Goat Farm Fattening Business "Gus Shor Farm" in Kanugrahan Village, Maduran, Lamongan is a strategic effort in increasing the productivity and sustainability of goat farming business. In this context, diversification strategies and productivity improvement are the main focus. The study aims to analyze local market potential, identify business diversification strategies, and design measures to increase goat farm productivity. Research methods used include field surveys, stakeholder interviews, and data analysis. The results showed that the demand for goat meat in the local market continues to increase, providing a great opportunity for "Gus Shor Farm" to develop a goat fattening business. Business diversification strategies include the development of processed goat products such as sausages, jerky, and goat cheese, which can increase the added value and attractiveness of products. In addition, productivity improvement is carried out through the application of technology and efficient management practices, including the use of high-quality feed, good livestock health management, and selection of superior goat breeds. By implementing this strategy, "Gus Shor Farm" can increase income, reduce financial risk, and contribute to economic and social development in Kanugrahan Village, Maduran, Lamongan.